A mega-aggregation framework synthesis of the barriers and facilitators to linkage, adherence to ART and retention in care among people living with HIV - Hendricks, Lynn (Syst Rev, 2021)
BACKGROUND: People living with human immunodeficiency virus (PLHIV) struggle with the challenges of living with a chronic disease and integrating antiretroviral treatment (ART) and care into their daily lives. The aims of this study were as follows: (1) to undertake the first mega-aggregation of qualitative evidence syntheses using the methods of framework synthesis and (2) make sense of existing qualitative evidence syntheses that explore the barriers and facilitators of adherence to antiretroviral treatment, linkage to care and retention in care for PLHIV to identify research gaps. METHODS: We conducted a comprehensive search and did all screening, data extraction and critical appraisal independently and in duplicate. We used the Kaufman HIV Behaviour Change model (Kaufman et al., 2014) as a framework to synthesise the findings using the mega-aggregative framework synthesis approach, which consists of 8 steps: (1) identify a clearly defined review question and objectives, (2) identify a theoretical framework or model, (3) decide on criteria for considering reviews for inclusion, (4) conduct searching and screening, (5) conduct quality appraisal of the included studies, (6) data extraction and categorisation, (7) present and synthesise the findings, and (8) transparent reporting. We evaluated systematic reviews up to July 2018 and assessed methodological quality, across reviews, using the Joanna Briggs Institute Critical Appraisal Checklist for Systematic Reviews. RESULTS: We included 33 systematic reviews from low, middle- and high-income countries, which reported on 1,111,964 PLHIV. The methodological quality of included reviews varied considerably. We identified 544 unique third-order concepts from the included systematic reviews, which were reclassified into 45 fourth-order themes within the individual, interpersonal, community, institutional and structural levels of the Kaufman HIV Behaviour Change model. We found that the main influencers of linkage, adherence and retention behaviours were psychosocial and personal characteristics—perceptions of ART, desires, fears, experiences of HIV and ART, coping strategies and mental health issues—interwoven with other factors on the interpersonal, community, institutional and structural level. Using this approach, we found interdependence between factors influencing ART linkage, retention and adherence and identified the need for qualitative evidence that explores, in greater depth, the complex relationships between structural factors and adherence, sociodemographic factors such as community violence and retention, and the experiences of growing up with HIV in low- and middle-income countries—specifically in children, youth, women and key populations. CONCLUSIONS: This is the first mega-aggregation framework synthesis, or synthesis of qualitative evidence syntheses using the methods of framework synthesis at the overview level. We found the novel method to be a transparent and efficient method for assessing the quality and making sense of existing qualitative systematic reviews. SYSTEMATIC REVIEW REGISTRATION: The protocol of this overview was registered on PROSPERO (CRD42017078155) on 17 December 2017. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13643-021-01582-z.